Exploring the Teaching Practice Experience of Pre-Service Teachers: Challenges and Learning Outcomes - Khalid, Sehrish; Zafar, Rizwan; Mahmood, Tariq (Pakistan Languages and Humanities Review, 2025)
This study explores students’ satisfaction with teaching practice during their preservice teacher education programs. The primary objective of this research was to assess how various aspects of the practicum contribute to or hinder student satisfaction. Teaching practice, often considered the capstone component of teacher education, offers preservice teachers an opportunity to apply theoretical knowledge in real classroom settings. A quantitative research design was employed, with data collected from 358 B.Ed. students enrolled in public and private teacher education institutions. A structured questionnaire was used to evaluate key dimensions such as instructional planning, mentor support, classroom management, institutional resources, and overall practicum structure. Statistical analyses—including descriptive statistics and linear regression—were conducted using SPSS. Key findings indicate that: Students reported high satisfaction with lesson planning support, teaching opportunities, and guidance from supervisors. Challenges were noted in areas such as classroom management, access to teaching materials, and mentor consistency. Students who received regular feedback and support from mentors showed higher levels of professional confidence and teaching engagement. A While most participants expressed overall satisfaction with the teaching practice, they also suggested improvements—such as extending the practicum duration, enhancing mentor quality, and providing clearer guidelines and more resources. These suggestions highlight disconnect between institutional expectations and the realities faced by student teachers in the field.